Impact of promoting self-care in nursing workload - Trettene, Armando dos Santos; Bertoncelo Fontes, Cassiana Mendes [UNESP]; Ribeiro Razera, Ana Paula; Gomide, Marcia Ribeiro (Univ Sao Paolo, 2016)
Objective: To assess the impact of promoting self-care in nursing workload and associate it to the variables: age, gender, socioeconomic status, education, marital status and number of children of caregivers. Methods: Prospective study with 31 children and their caregivers. Participants were assessed at two moments, 1st and 2nd hospitalization, the nursing workload was measured by the Nursing Activities Score (NAS). Results: The mean NAS in the 1st hospitalization was 60.9% and in the 2nd hospitalization was 41.6%, that is, 14.6 and 9.9 hours of nursing, respectively. The nursing workload on the first day of hospitalization was higher compared to the last day, both for the 1st (p<0.001) and for the 2nd hospitalization (p<0.001), and higher in the first (p<0.001) and in the last day (p=0.025) in the 1st hospitalization. Comparing the 1st hospitalization to the 2nd hospitalization, the first was higher (p<0.001), and NAS items related to the training of self-care was influenced (p<0.001). Conclusion: The nursing workload associated to self-care promotion corresponded to 14.6 hours and was higher than determined by the existing legislation.
Keywords: Nursing; Self-care; Workload; Personnel Downsizing; Subacute Care; Pierre Robin Syndrome